ZnO nanostructures directly grown on paper and bacterial cellulose substrates without any surface modification layer - Costa, Saionara V.; Gonçalves, Agnaldo S.; Zaguete, Maria A. [UNESP]; Mazon, Talita; Nogueira, Ana F. (Royal Society of Chemistry (RSC), 2013)
In this report, hierarchical ZnO nano- and microstructures were directly grown for the first time on a bacterial cellulose substrate and on two additional different papers by hydrothermal synthesis without any surface modification layer. Compactness and smoothness of the substrates are two important parameters that allow the growth of oriented structures. © 2013 The Royal Society of Chemistry.
Keywords: carbon nanotube; cellulose; nanomaterial; zinc oxide; anisotropy; bacterial membrane; biosensor; chemical modification; chemical structure; Gluconacetobacter xylinus; nonhuman; structure analysis; surface property